Innovation, creativity and tourism - Magadán Díaz, Marta; Rivas García, Jesús Israel (Emerald, 2022)
Purpose - The main aim of this chapter is to show the paramount role that both creativity and innovation have in order to state competitive advantages in tourism. Methodology/approach - The approach is based both on literature review and on various business cases to underline the ideas derived from the literature review. Findings - An entrepreneurial mind must be creative and innovative. This simple idea takes a special value in tourist businesses because of the need to survive in a global market full of competitive actors, dynamism and volatility of preferences in consumers' attitudes. Research limitations/implications - This chapter is an approaching essay based mainly on a general literature review supported with several case studies. Practical implications - Tourism entrepreneurs must take into account the role that creativity and innovation have for their business plans. These two dimensions are the head and tail of the same coin that will help them not only to create value for tourist customers but also to make the difference between them and their competitors. Originality/value - This chapter shows the connections between creativity, innovation and competitive advantages, and their critical value for any entrepreneur who wants to deploy a successful business venture. © 2018 by Emerald Publishing Limited.
Es un capítulo del libro: Magadán, M. and Rivas, J. (2018), "Innovation, Creativity and Tourism", Sotiriadis, M. (Ed.) The Emerald Handbook of Entrepreneurship in Tourism, Travel and Hospitality, Emerald Publishing Limited, Bingley, pp. 71-88.
Keywords: competence; competitive advantage; creativity; entrepreneur; innovation; Scopus(2)